PERANCANGAN SISTEM INFORMASI PENYELEKSIAN PENERIMA BANTUAN PERUMAHAN PADA KECAMATAN LASIOLAT KABUPATEN BELU - Igon, Skolastika Siba; Meo, Meliana O.; Bere, Febrianty (STIKOM Uyelindo Kupang, 2020)
Based on the latest data from the Department of Population and Civil Registration in Belu Regency, the area of ??Belu Regency is 1,285 Km2, with a population of 229,561 people. From this data, Lasiolat District is one of the Districts in Belu District where there are still 299 uninhabitable houses and 1,360 housing units out of 1,659 families, with a total population of 7,171 people, an area of ??13,200 Km2. Therefore, the local government through the Department of Housing and Settlements provides housing assistance to deal with problems arising from the inability of low income people. However, Lasiolat District officials still have difficulty in selecting people who are entitled to get help. Because in the selection process it is still difficult to record the large number of people manually, it takes a long time because the local government through the Housing and Settlement Office only provides as many as 100 housing units. The limited housing assistance provided, the selection process for beneficiaries who are eligible for assistance, the Department checks the data of beneficiaries through the District officials to determine citizenship, income, land ownership, type of house, building and marital status. Errors in selecting beneficiaries can result in assistance being given to recipients who do not deserve assistance. Therefore we need a system that can be used to make selections with the main objective of overcoming the problems encountered in the selection process that is currently underway. In this research, an information system for selecting housing beneficiaries will be built using the Fuzzy AHP method. The system is built based on the website. The final result expected from this research is to be able to assist the Sub-district officials in selecting housing recipients correctly and appropriately.